An Overview of Foreign Trade and Economic Relations of the Republic of Belarus with the EU and Lithuania - Cohen, Viktorija; Akulich, Ivan; Sverlov, Aleksey (Ekonomika, 2018)
Foreign trade fosters not only companies but national economies to maximize their gains for the benefit of a better living standard. In developing countries, such as Belarus, the volume of foreign trade depends on the path of liberalization and integration into the trade with the EU. This paper analyzes foreign trade and economic relations between the EU, Lithuania and Belarus.